Bisnis Transportasi dalam Pusaran Globalisasi - Mutimatun Ni’ami (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
This study aims to examine the differences between conventional taxis and online taxis and whether the existing legal regulations are sufficient to regulate the two modes of transportation. The author's curiosity comes from seeing the past when taxis were considered a luxury means of transportation that people rarely use except for emergencies, so city buses and public transportation become the choice of citizens. The choice that was "forced" to be taken considering the low cost and far coverage. Now, when online taxis offer low costs and easy access, the means of transportation that have become "gods" have fallen. The drivers gasped, the transportation entrepreneurs were distracted to finance their business empire and the passengers were no longer greeted by buses and public transportation. This research is a sociological legal research which makes a phenomenon that exists in society and its influence on existing legal rules. The research results show that the difference between conventional taxis and online taxis lies in the amount of tariff, standardization of services, determination of routes and special features and legal protection. The government needs to be firm in regulating the existence of online transportation, given the potential for conflict over disparity in tariff differences and the importance of legal protection for drivers and passengers in driving safety.Keywords:Online Taxi; Conventional Taxi; Legal.